Analysis of the Need For Animated Video Teaching Materials in Beginning Reading Instruction for First Grade Elementary School - Widyastuti, Ana; Solihati, Nani; Zulaiha, Siti (Soegijapranata Catholic University, 2025)
In the realm of education, the instruction of early reading in first grade of Elementary School holds a pivotal role in establishing the foundational literacy skills for students. However, educators often encounter challenges in delivering these instructional materials. One proposed solution is the utilization of teaching aids in the form of animated videos. The aim of this study is to analyze the necessity of using animated video teaching materials for early reading in first grade of elementary school and to comprehend the extent to which teachers' needs are related to the instruction of early reading for their students. Through this research, it is anticipated to provide recommendations to all educational stakeholders to understand and address the requirements for the utilization of digital teaching aids, specifically animated videos, in the instruction of early reading in first grade of elementary school. This research employs a qualitative descriptive method involving 30 class teachers from 23 elementary schools as the sample. The findings indicate that educators still tend to rely on conventional teaching aids, particularly concerning the utilized instructional media. It is found that there is a need for diverse and complex digital teaching materials, specifically animated videos, as well as the necessity for support from all relevant stakeholders to fulfill the educators' needs in elementary schools. The implications of this research are expected to enhance students' proficiency in early reading instruction for first-grade students using animated video teaching aids in the current digital era.